The Impact of Corporate Social Responsibility Disclosure on the Cost of Debt Evidence from Finland : A Comparative Analysis of Pre and Post Covid Periods - Dissanayaka Mudiyanselage, Kavindiya Madhumadhawi Dissanayaka (My University, 2026)
In recent decades, transparency and responsible corporate behaviour have received greater attention from stakeholders, which has led to the Corporate Social Responsibility Disclosures (CSRD) playing a significant role in today's financial markets. With financial markets adopting the use of non-financial information in decision-making processes, the CSRD has become a critical factor in determining financing costs. Thus, in influencing key financial metrics, especially the Cost of Debt (COD), CSRD plays a significant role. Even though the significance of CSRD is widely recognized, its impact on COD is still debatable in academia, as prior studies have reported mixed findings regarding the association between CSRD and COD. As one of the top rankers in corporate transparency, stakeholder trust, and sustainability performance, Finland has a corporate environment where CSRD is well developed and highly valued. Thus, this study explores the association between CSRD and COD firms listed on the Helsinki Stock Exchange. By extending the scope, the study investigates whether creditors place greater value on CSRD during the Covid-19 period, as in the context of Finland, exploration of CSRD and COD during times of crises is still limited. The study is relying on key theories of signaling, stakeholder, and legitimacy, which offer different explanations about the impact of CSRD on COD. The study uses a fixed effect regression model in the analysis, and the panel dataset consists of a sample of 77 listed firms covering the period from 2014 to 2023. The result suggests that CSRD does not significantly affect the firm's cost of borrowing in Finland. Supporting this, the findings reveal that a positive and statistically insignificant association exists between CSRD and COD. Additionally, in terms of the role of Covid- 19, the results reveal that the interaction term was negative but statistically insignificant. This finding emphasizes that the association between CSRD and COD has not been affected by Covid- 19 in a statistically significant way. This study contributes to the existing literature by providing empirical evidence on the association between CSRD and a firm's COD financing in the Finnish context and directs future research toward combining qualitative methods to provide further contextual information on how lenders utilize CSR information in their lending decision-making and risk assessments.
Keywords: COVID-19; corporate responsibility; transparency; costs; disclosure of information; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance